Adipolin protects against renal injury via PPARα-dependent reduction of inflammasome activation - Lixin Fang; Koji Ohashi; Satoko Hayakawa; Hayato Ogawa; Naoya Otaka; Hiroshi Kawanishi; Tomonobu Takikawa; Yuta Ozaki; Kunihiko Takahara; Minako Tatsumi; Mikito Takefuji; Yuuki Shimizu; et al. (iScience, 2023)
Summary: Although chronic kidney disease (CKD) is a major health problem worldwide, its underlining mechanism is incompletely understood. We previously identified adipolin as an adipokine which provides benefits for cardiometabolic diseases. Here, we investigated the role of adipolin in the development of CKD. Adipolin-deficiency exacerbated urinary albumin excretion, tubulointerstitial fibrosis and oxidative stress of remnant kidneys in mice after subtotal nephrectomy through inflammasome activation. Adipolin positively regulated the production of ketone body, β-hydroxybutyrate (BHB) and expression of a catalytic enzyme producing BHB, HMGCS2 in the remnant kidney. Treatment of proximal tubular cells with adipolin attenuated inflammasome activation through the PPARα/HMGCS2-dependent pathway. Furthermore, systemic administration of adipolin to wild-type mice with subtotal nephrectomy ameliorated renal injury, and these protective effects of adipolin were diminished in PPARα-deficient mice. Thus, adipolin protects against renal injury by reducing renal inflammasome activation through its ability to induce HMGCS2-dependent ketone body production via PPARα activation.